The Influence of the Membership Program on Customer Loyalty of Seventeen Garage Bekasi Workshops - Ilyas Munaf, Faris; Juni Priansa, Donni (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
In a business, membership or membership is often used so that customers get various kinds of attractive promos. Membership or membership is an activity in achieving formal status support in a business. The membership or membership system at the Seventeen Garage workshop is that every customer who is interested in becoming a member will be given a member card and will be stamped for every 1x service. If you have done 10x service, you will get the 11th free service. and how does the influence of membership on customer loyalty to visitors to the Bekasi Seventeen Garage Workshop This research is a descriptive verification research. Descriptive is used to explore the variables studied while verification is used to measure the relationship of variables. The population of this study are students in Bekasi City who have attended the Bekasi Seventeen Garage Workshop. The population size is known, thus the sampling uses the Slovin formula. which results in a total sample of 101, which is then rounded down to 100 samples. This study found that the membership carried out by the Bekasi Seventeen Garage workshop was in the high category; Seventeen Garage Bekasi customer loyalty is in the sufficient category; and membership has a significant effect on customer loyalty with a very strong level of influence classification.